Benthic diel oxygen variability and stress as potential drivers for animal diversification in the Neoproterozoic-Palaeozoic - Emma U. Hammarlund; Anuraag Bukkuri; Magnus D. Norling; Mazharul Islam; Nicole R. Posth; Etienne Baratchart; Christopher Carroll; Sarah R. Amend; Robert A. Gatenby; Kenneth J. Pienta; Joel S. Brown; Shanan E. Peters; et al. (Nature Communications)
Abstract The delay between the origin of animals in the Neoproterozoic and their Cambrian diversification remains perplexing. Animal diversification mirrors an expansion in marine shelf area under a greenhouse climate, though the extent to which these environmental conditions directly influenced physiology and early organismal ecology remains unclear. Here, we use a biogeochemical model to quantify oxygen dynamics at the sunlit sediment-water interface over day-night (diel) cycles at warm and cold conditions. We find that warm temperatures dictated physiologically stressful diel benthic oxic-anoxic shifts over a nutrient-rich shelf. Under these conditions, a population-and-phenotype model further show that the benefits of efficient cellular oxygen sensing that can offer adaptations to stress outweigh its cost. Since diurnal benthic redox variability would have expanded as continents were flooded in the end-Neoproterozoic and early Palaeozoic, we propose that a combination of physiological stress and ample resources in the benthic environment may have impacted the adaptive radiation of animals tolerant to oxygen fluctuations.